Y (3940) as a mixed charmonium-molecule state - Albuquerque, R. M. [UNESP]; Dias, J. M.; Nielsen, M.; Zanetti, C. M. (American Physical Society (APS), 2014)
Using the QCD sum rules approach, we study the mass and the decay widths of the Y(3940) state, assuming that it can be described by a mixed charmonium-molecule scalar state, i.e., a mixture between the χc0 charmonium and D*D̄* molecule. Using a current with JPC=0++, we estimate for the mixing angle, θ=(76.0±5.0)°, resulting in a mass value of MY=(3.95±0.11)GeV, which is in reasonable agreement with the experimental mass of the Y(3940) state. For the decay width, we evaluate the channels Y→J/ψω and Y→γγ. We find the values ΓY→J/ψω≈(1.7±0.6)MeV and ΓY→γ γ≈(1.6±1.3)KeV, respectively. We also study the decay process of this state into channels containing DD̄ mesons in the final state. The result for the order of magnitude of the product ΓY→γγ ×ΓY→J/ψω∼O(103)KeV2 is also in reasonable agreement with the experimental data. We thus conclude that the present description of the Y(3940) as a mixed charmonium-molecule state is a possible scenario to explain the structure of such a state. © 2014 American Physical Society.